A case of carbon dioxide embolism during the transperineal approach in total pelvic exenteration for advanced anorectal cancer. Issue 1 (12th August 2020) - Matsumoto, Yoshiko; Yoshimatsu, Gumpei; Munechika, Taro; Kajitani, Ryuji; Taketomi, Hirotaka; Nagano, Hideki; Komono, Akira; Morimoto, Mitsuaki; Aisu, Naoya; Yoshida, Yoichiro; Hasegawa, Suguru
Abstract: The transanal and transperineal endoscopic approaches are useful advanced surgical options for removing rectal and anorectal cancers. Intraoperative carbon dioxide (CO2 ) embolisms, however, have been increasingly reported as potentially fatal complications associated with surgery employing these approaches. We report our experience with a CO2 embolism that was detected because of a sudden drop in end‐tidal CO2 with decreasing saturation of percutaneous arterial oxygen during total pelvic exenteration using the transperineal endoscopic approach under pneumopelvis/pneumoperitoneum. Transesophageal echocardiography confirmed that it was a CO2 embolus. We reversed the pneumopelvis and pneumoperitoneum, which alleviated the cardiopulmonary problems, and the surgery then proceeded to achieve R0 resection. The patient was discharged without severe complications other than the CO2 embolism.